A new species of Colletes (Hymenoptera: Apoidea: Colletidae) from northern Florida and Georgia, with notes on the Colletes of those states - Hall, H Glenn; Almquist, David T; Ascher, John S (Journal of Melittology, 2016)
Colletes ultravalidus Hall & Ascher, new species, is described from several sites in northwestern Florida and southeastern Georgia.  It is a member of the inaequalis species group, very similar to C. validus Cresson, a specialist of Ericaceae, but can be distinguished by an even more elongate malar area and the absence of conspicuous tergal fascia.  Colletes ultravalidus has been found flying from early winter to early spring when it forms nest aggregations in xeric sites adjacent to shrub bog or basin swamp, the habitat of Pieris phyllyreifolia (Hook.) DC. (Ericaceae), the most likely, but as yet unconfirmed, host plant of the new species.  State records of Colletes for Florida and Georgia are reviewed and discrepancies in taxonomy and distributional limits between Stephen’s 1954 revision of the genus and Mitchell’s 1960 monograph of eastern North American bees are noted.  We concur with Stephen that the distributions of several taxa in Colletes are more limited than that reported by Mitchell.